2011
DOI: 10.1007/s00335-011-9356-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the translocation breakpoints in the Ts65Dn and Ts1Cje mouse lines: relevance for modeling down syndrome

Abstract: Down syndrome (DS) is the most frequent genetic disorder leading to intellectual disabilities and is caused by three copies of human chromosome 21. Mouse models are widely used to better understand the physiopathology in DS or to test new therapeutic approaches. The older and the most widely used mouse models are the trisomic Ts65Dn and the Ts1Cje mice. They display deficits similar to those observed in DS people, such as those in behavior and cognition or in neuronal abnormalities. The Ts65Dn model is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
204
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(213 citation statements)
references
References 53 publications
9
204
0
Order By: Relevance
“…12 Ts65Dn mice carry an unbalanced derivative, Ts (17 16 )65Dn, of a balanced translocation, which was randomly induced by irradiation. 12 The Ts (17 16 )65Dn chromosome consists of the entire genomic region distal to Mir155 on Mmu16 and a subcentromeric region on Mmu17, which is not syntenic to Hsa21 13,14 (Supplementary Table S1). The second postnatally viable mouse model of DS is Ts1Cje, which carries an unbalanced derivative, Ts (12 16 ) 1Cje, of a balanced translocation, which was induced by gene-targeting in mouse ES cells.…”
Section: Modeling Ds At the Early Stagementioning
confidence: 99%
See 2 more Smart Citations
“…12 Ts65Dn mice carry an unbalanced derivative, Ts (17 16 )65Dn, of a balanced translocation, which was randomly induced by irradiation. 12 The Ts (17 16 )65Dn chromosome consists of the entire genomic region distal to Mir155 on Mmu16 and a subcentromeric region on Mmu17, which is not syntenic to Hsa21 13,14 (Supplementary Table S1). The second postnatally viable mouse model of DS is Ts1Cje, which carries an unbalanced derivative, Ts (12 16 ) 1Cje, of a balanced translocation, which was induced by gene-targeting in mouse ES cells.…”
Section: Modeling Ds At the Early Stagementioning
confidence: 99%
“…Ts (12 16 )1Cje chromosome carries the entire genomic region distal to Sod1 on Mmu16 with Sod1 inactivated 13,15 (Supplementary Table S1). Recent analyses showed a heterozygous deletion on Mmu12 in Ts1Cje mice, which is not syntenic to Hsa21.…”
Section: Modeling Ds At the Early Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Down syndrome is a common genetic disorder, occurring in 1 of 700-800 births, with a gender ratio of three boys to two girls (Duchon et al, 2011). It has been reported that there are more than 217,800 cases a year across the world.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there are more than 217,800 cases a year across the world. The clinical picture of this syndrome is complex; more than 80 phenotypes have been observed in individuals, including intellectual disabilities with delayed learning and cognition, congenital anomalies such as congenital heart disease and childhood leukemia, and the appearance of an Alzheimer-like disease during aging (Fillon-Emery et al, 2004;Duchon et al, 2011;Wilcock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%